The Association Between Thyroid Diseases and Alzheimer’s Disease in a National Health Screening Cohort in Korea - Kim, Ji Hee; Lee, Heui Seung; Kim, Yoo Hwan; Kwon, Mi Jung; Kim, Joo-Hee; Min, Chan Yang; Yoo, Dae Myoung; Choi, Hyo Geun (Frontiers in Endocrinology, 2022)
Objectives: Thyroid dysfunction is linked to an increased risk of cognitive impairment. However, studies on the relationships between thyroid diseases and Alzheimer’s disease (AD) have reported conflicting results. We investigated the associations between several thyroid diseases and AD in a nested case-control study. Methods: A total of 1,977 participants with AD were identified by claims data from 2002-2015 among a random sample of half a million people in the Korean National Health Insurance database. We recruited 16,473 age- and sex-matched (1:4 ratio) control participants and applied conditional logistic regression to estimate the relationships between thyroid diseases and AD, with adjustments for potential confounders, such as basic demographics, lifestyle factors, and various medical conditions or comorbidities. Results: The prevalence rates of hypothyroidism (odds ratio [OR]=1.14, 95% confidence interval [CI]=1.00-1.30), thyroiditis (OR=1.22, 95% CI=1.05-1.40), and hyperthyroidism (OR=1.13, 95% CI=1.01-1.28) were significantly higher in participants with AD than in control participants after adjustment for confounders. Conclusion: In this large national sample, we found significant relationships between several thyroid diseases and AD. Despite of the need for further investigation, these findings could better support to appreciate the pathophysiology of AD.